ANALISIS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENEBANGAN LIAR HUTAN PRODUKSI ALUR LEBAH DI KABUPATEN LANGKAT (Studi Kasus Putusan Pengadilan Negeri Stabat No. 107/Pid.B/LH/2021 /PN STB): Studi Kasus Putusan Pengadilan Negeri Stabat No. 107/Pid.B/LH/2021 /PN STB - Nabila, Raihan (Universitas Harapan Medan, 2024)
Forests are vital natural resources that provide oxygen, habitat and maintain ecosystem balance. However, unlawful illegal logging threatens forest sustainability, causing environmental damage and significant economic losses. In Indonesia, despite regulations to tackle this practice, illegal logging remains widespread, fueled by corruption and weak law enforcement. The economic impact of illegal logging is also significant. Despite being considered an illegal activity, the trade in illegally logged timber reaches a huge value in the global market. This research aims to analyze the factors that influence illegal logging and its impacts, especially through Supreme Court case Number 107/Pid.B/LH/2021. The research method used is a normative and analytical approach, using data obtained from literature studies, analysis of legal documents, and review of court decisions. Primary sources included laws and court decisions, while secondary sources included academic literature and research reports. Qualitative methods were used to explore in-depth perspectives on the impacts of illegal logging. The results confirm that illegal logging has far-reaching impacts on the environment and society. As stipulated in Law No. 18/2013 on Illegal Logging, stricter law enforcement, strengthened regulations, as well as increased public awareness are needed to tackle this illegal practice, so that the sustainability of forest ecosystems and natural resource management can be maintained.